River water treatment using electrocoagulation for removal of acetaminophen and natural organic matter - Kumari, Shweta; Kumar, R. Naresh (Chemosphere (Oxford), 2021)
Electrocoagulation (EC) was assessed for removal of acetaminophen and natural organic matter (measured as UV254) from river water. Process was assessed for time, electrode materials, inter electrode distance, and voltage. Best conditions for removal of acetaminophen and UV254 absorbance were 60 min reaction time, aluminum-aluminum electrodes, 2 cm inter electrode distance, and 9 V. Acetaminophen tested at 1, 2, 5, 10, and 20 mg L−1 showed that treatment efficiency decreased as the concentration increased. The main mechanism for removal of acetaminophen was H bonding with Al(OH)3 flocs; this was confirmed by XRD and FT-IR spectrum. Pseudo-second order kinetics model exhibited a good fit on experimental data for acetaminophen removal at different concentrations. Univariate ANOVA indicated statistically significant difference between treatments for acetaminophen removal (F2.76 = 136, P = <0.001). A significant linear correlation was found between UV254 absorbance and acetaminophen removal at different concentrations. Preliminary analysis suggest that EC will cost US$ 0.22/m3 for river water treatment. The lab-scale EC process was compared with a full-scale water treatment plant for removal of natural organic matter. Water treatment plant after multiple levels of purification was not able to fully remove UV254 absorbance whereas EC treatment showed good efficiency. [Display omitted] •Electrocoagulation effectively removed acetaminophen at 1 mg L−1•Main removal mechanism was H bonding of acetaminophen on Al(OH)3 flocs•Acetaminophen removal shows good correlation with UV254 absorbance removal•Conventional water treatment plant is unable to remove UV254 absorbance completely•Electrocoagulation can be suitable replacement for coagulation-flocculation